An empirical investigation of the academic performance in management education: Case study of the University of Malaya MBA Program - Sulaiman, Ainin (2004)
The Master’s of Business Administration (MBA) program is one of the most popular management education program in the country. University of Malaya has been offering this program since 1981. It is known to be among the most comprehensive and rigorous program in the country. This study will examine the academic performance of these MBA students. It investigates the impacts of several variables to the academic performance of the MBA students. Among the variables examined are qualifications (type of degree and undergraduate cumulative grade point average), age (with age and experience as covariates), gender, and ethnicity. Preliminary analysis indicates that qualifications and age have a correlation with the students’ academic performance. The paper also discusses the implications of the study to management education especially the admission requirement into the MBA program.